The potential of folklore as biodiversity learning resources in high school - Rexy Maulana Dwi Karmadi; S. Suhartini; Ahmad Adnan Mohd Sukri (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Learning resources are everything that can be used to facilitate the learning process. Folklore is one of the cultural products that can be innovated as a biodiversity learning resource in high school. This study reviewed relevant literature regarding folklore from various regions of Indonesia to examine and analyse the potential of folklore as a learning resource for biodiversity. The descriptive analysis revealed that the contents of folklore can be used to study examples of the biodiversity level, the regional distribution of Indonesia’s biodiversity, flora and fauna characteristics of Oriental, Australian, and Transitional, benefits of biodiversity and its conservation efforts. In addition, folklore as a learning resource also has the potential to develop student competencies such as environmental care, creative thinking, critical thinking, and problem-solving. However, the folklore content cannot describe all the material on biodiversity, therefore it must be combined with other learning resources for use in the biodiversity learning process.